Detection and Analysis of Protein Profile on Rice Infected by Stunting Virus with Different Severity on Ciherang and Situ Bagendit Varieties - Selvi Helina; Sri Sulandari; Sedyo Hartono; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2019)
Rice stunt virus is one of the limiting factors in the decline of rice production in Indonesia. The virus consists of rice grassy stunt virus (RGSV) and rice ragged stunt virus (RRSV) that is transmitted by brown planthopper (WBC) in a persistent propagative manner. This study aimed to determine the presence of rice stunt virus in Bantul, Yogyakarta through fast detection using RT-PCR. It also aimed to learn the pattern of total protein profile of healthy and infected rice plants by the virus on different severity level in the field. The results showed that rice varieties of Ciherang and Situ Bagendit in Bantul were infected with RGSV and RRSV. They were classified as mild, moderate, severe, and failure in severity level. Homology analysis using BioEdit showed that the nucleotide sequence of RGSV in Bantul isolate had the highest percentage of nucleic acids similarity with Klaten isolate (98.1%). Meanwhile, RRSV of Bantul isolate had the highest percentage of nucleic acids similarity to Philipines isolate (99.5%). Analysis of protein profiles using SDS-PAGE showed a pattern of protein profiles formed on rice infected with the virus at different severity levels which was not found in healthy rice. These proteins presumably were nonstructural p5 and nucleocapsid protein (NCP) of RGSV with a molecular weight of ~22 and 34-35 kDa; and viral spike protein and protein capsid (S8) of RRSV with MW ~39 and ~43 kDa.